Can learners use morphosyntactic cues to facilitate processing? Evidence from a study of gender agreement in Hindi. (3rd July 2018) - Covey, Lauren; Gabriele, Alison; Fiorentino, Robert
ABSTRACT: This study investigates L2 learners' ability to use morphosyntactic gender as a predictive cue during the processing of Hindi agreement dependencies. Nine L2 learners of low-intermediate proficiency and nine highly proficient multilingual speakers who consider Hindi one of their dominant languages were tested using a speeded picture-selection task. Results indicate that both L2 learners and multilingual speakers of Hindi used gender information to rapidly facilitate access to a target noun during processing, although because the facilitative effects were at the target noun, rather than preceding it, these facilitative effects do not provide unambiguous evidence for prediction. Participants' processing speed in a control condition was also correlated with sensitivity to the gender cue, which is in line with accounts that posit that the ability to use linguistic cues during processing is modulated by individual differences.